Two Variant Modeling Methods for MBPLE at Airbus. Issue 1 (26th September 2022) - Forlingieri, Marco; Weilkiens, Tim
Abstract: Product Line Engineering (PLE) is a fundamental component of systems engineering. As postulated in INCOSE's Vision 2025, Model‐Based Systems Engineering (MBSE) is becoming the norm for systems engineering. Thus, we need to integrate PLE into MBSE. An important aspect of this integration is the definition of model‐based methods. This paper defines two possible approaches for variant modeling with SysML applied at Airbus and provides insights into their application in practice.